A construção da usina hidrelétrica Barra Bonita e a relação homem-natureza: vozes dissonantes, interesses contraditórios (1940-1970) - Massei, Roberto (2007)
This doctoral theses tried to discuss and questionate the technologic instrumental role at Barra Bonita´s power plant construction, at a space in the Tiete´s River, in the central Region of São Paulo, and the social, economic, environmental and cultural impact caused by it´s lake mainly to the brickmaker-ceramic population from Barra Bonita and around it. This paper is orientated, theoretically, by Oral and Material Culture History. And it has as a temporal mark at the 1940´s and 1970´s. From brickmakers workers, former inhabitants and technicians (engineers) experiences, who lived or participated directly in the power plant construction, was possible to stablish the relation between technology, nature, environment and society that supports all the material life. The lake overflew 34 thousand hectares, the majority was the meadows of the River, and it changed very much the relation between the human being and the nature. This change can be clearly noticed at the clay extraction and transformation that was used - and is still used to produce tile and brick at the red ceramic from the city and around it. New techniques or strategies were developed in order to obtain the submerged clay, increasing even more the environment aggression. The production process has been modified as well and according to the testimonies, it is possible to observe the mechanical acceleration and the population´s changing in relation to their material and symbolic world. At the beginning of last century, many families from Barra Bonita moved to Ourinhos to explore the same activity, it occurred the same process. The material culture study assumes the comprehension of the way the human-being has transformed the environment in which he has lived and still lives through techniques he has made his objects and has built his material world